The protection of vulnerable persons through transitional justice: The accreditation of victims in the Special Jurisdiction for Peace proceedings - Idárraga Martínez, Ana María (2021)
This paper analyzes the process of accreditation of victims in the Special Jurisdiction for Peace (JEP) procedure, in accordance with the requirements of the 100 Brasilia Rules. To this end, it will study the concept of «victim» in both the 100 Brasilia Rules and the SJP, as well as its consequences for the protection of vulnerable populations. Then, it will address the process of accreditation of the victims of the Colombian armed conflict before the JEP, as well as its progress and challenges concerning the rights of the vulnerable population, especially their access to justice. The conclusions will focus on the progress, challenges, and recommendations that emerge from the above analysis.